2021
DOI: 10.3390/cells10020280
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory Impact of Adipose-Derived Mesenchymal Stem Cells of Ankylosing Spondylitis Patients on T Helper Cell Differentiation

Abstract: The domination of pro-inflammatory Th subsets (Th1, Th17) is characteristic of ankylosing spondylitis (AS). Mesenchymal stem cells (MSC) were reported to normalize Th imbalance, but whether MSCs from AS adipose tissue (AS/ASCs) possess such properties is unknown. We examined AS/ASCs’ impact on Th-cell differentiation, using healthy donors ASCs (HD/ASCs) as a control. The assessment of the expression of transcription factors defining Th1 (T-bet), Th2 (GATA3), Th17 (RORc), and Treg (FoxP3) subsets by quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…ADSC-mediated effects on T cells proliferation and differentiation depend on several mechanisms, including cell-to-cell contact and secretion of soluble factors [ 50 , 51 ]. Accumulated evidence has proved that ADSC-Exos, carrying complex biological information, including mRNAs, microRNAs (miRNAs), and soluble proteins, interact with target cells and influence their fate in tissue regeneration and remolding [ 52 , 53 ].…”
Section: Related Workmentioning
confidence: 99%
“…ADSC-mediated effects on T cells proliferation and differentiation depend on several mechanisms, including cell-to-cell contact and secretion of soluble factors [ 50 , 51 ]. Accumulated evidence has proved that ADSC-Exos, carrying complex biological information, including mRNAs, microRNAs (miRNAs), and soluble proteins, interact with target cells and influence their fate in tissue regeneration and remolding [ 52 , 53 ].…”
Section: Related Workmentioning
confidence: 99%
“…This study revealed that HDAC4 was reduced in patients with AS compared with HCs and DCs; meanwhile, HDAC4 could distinguish patients with AS from HCs and DCs. Possible explanations could be that: (1) low expression of HDAC4 might promote the differentiation of Th17 cells and inflammation, thus leading to AS (2,18,28) in this study, patients with OA were served as DCs. Compared with patients with OA, patients with AS are characterized by immune system dysregulation (29,30).…”
Section: Discussionmentioning
confidence: 94%
“…Meanwhile, HDAC4 modulates inflammation in diverse pathological conditions, such as rheumatoid arthritis, asthma, and atherosclerosis, while inflammation is one of the hallmarks of autoimmune diseases (8,(13)(14)(15). Furthermore, HDAC4 can regulate the differentiation of T helper (Th) 17, which plays a vital role in the progression of AS by increasing the level of proinflammatory cytokines and thus directly aggravating AS (16)(17)(18); meanwhile, it is also suggested that Th17 participates in the bone remodeling in AS (19). However, apart from the experimental findings, few studies have explored the clinical implication of HDAC4 in autoimmune diseases such as AS, let alone its relevance to treatment response in AS.…”
Section: Introductionmentioning
confidence: 99%
“…One of the potential functions by which hASCs can modulate immune responses is their capability to induce and/or expand a regulatory and anti-inflammatory T cell phenotype (CD4 + CD25 high FoxP3 + ) (Najar et al 2010b ; Ivanova-Todorova et al 2012 ; Engela et al 2013 ; Karaöz et al 2016 ; Skalska et al 2017 ; Yousefi et al 2019 ; Bi et al 2020 ; Fakhimi et al 2019 ; Fiori et al 2021 ; Kuca-Warnawin et al 2021a ; Mahmoud et al 2023 ). Regulatory T cells (Tregs) have been shown to restrain excessive inflammatory responses in autoimmune diseases.…”
Section: Hasc Induction Of Tregs: Specific Immunomodulatory Mechanismmentioning
confidence: 99%